ANALYSIS OF BUDGET PREPARATION AT SMK NEGERI 5 SURABAYA, EAST JAVA - saputri, marisa catur; wuryani, eni (Universitas Dr. Soetomo, 2021)
The research aims to examne the budgeting that applied in the public sector. The sample used was one of the public schools there in Surabaya. In this research, the type of data used is primary data which is obtained directly from informants and supported by secondary data in the from of budget reports and school budget realization. The data analysis technique used is the reduction and validity test of the data obtained through field research, interviews and documentation studies. That the making and realization of budgets on 5 Surabaya education schools have been running. Will do well by obeying the rules set by the governor of east Java.